Cytotoxicity and Genotoxicity of Nanosized and Microsized Titanium Dioxide and Iron Oxide Particles in Syrian Hamster Embryo Cells. - Guichard, Yves; Schmit, Julien; Darne, Christian; Gaté, Laurent; Goutet, Michèle; Rousset, Davy; Rastoix, Olivier; Wrobel, Richard; Witschger, Olivier; Martin, Aurélie; Fierro, Vanessa; Binet, Stéphane (Annals of Occupational Hygiene, 2012)
Potential differences in the toxicological properties of nanosized and non-nanosized particles have been notably pointed out for titanium dioxide (TiO2) particles, which are currently widely produced and used in many industrial areas. Nanoparticles of the iron oxides magnetite (Fe3O4) and hematite (Fe2O3) also have many industrial applications but their toxicological properties are less documented than those of TiO2. In the present study, the in vitro cytotoxicity and genotoxicity of commercially available nanosized and microsized anatase TiO2, rutile TiO2, Fe3O4, and Fe2O3 particles were compared in Syrian hamster embryo (SHE) cells. Samples were characterized for chemical composition, primary particle size, crystal phase, shape, and specific surface area. In acellular assays, TiO2 and iron oxide particles were able to generate reactive oxygen species (ROS). At the same mass dose, all nanoparticles produced higher levels of ROS than their microsized counterparts. Measurement of particle size in the SHE culture medium showed that primary nanoparticles and microparticles are present in the form of micrometric agglomerates of highly poly-dispersed size. Uptake of primary particles and agglomerates by SHE exposed for 24 h was observed for all samples. TiO2 samples were found to be more cytotoxic than iron oxide samples. Concerning primary size effects, anatase TiO2, rutile TiO2, and Fe2O3 nanoparticles induced higher cytotoxicity than their microsized counterparts after 72 h of exposure. Over this treatment time, anatase TiO2 and Fe2O3 nanoparticles also produced more intracellular ROS compared to the microsized particles. However, similar levels of DNA damage were observed in the comet assay after 24 h of exposure to anatase nanoparticles and microparticles. Rutile microparticles were found to induce more DNA damage than the nanosized particles. However, no significant increase in DNA damage was detected from nanosized and microsized iron oxides. None of the samples tested showed significant induction of micronuclei formation after 24 h of exposure. In agreement with previous size-comparison studies, we suggest that in vitro cytotoxicity and genotoxicity induced by metal oxide nanoparticles are not always higher than those induced by their bulk counterparts.